1973
DOI: 10.1016/0028-3908(73)90005-1
|View full text |Cite
|
Sign up to set email alerts
|

Acetylseco hemicholinium-3, a new choline acetyltransferase inhibitor useful in neuropharmacological studies

Abstract: Summary-Describedare the synthesis and some aspects of the pharmacology of acetylseco hemicholinium-3 (acetylseco HC-3), the acetylated open ring analogue of hemicholinium-3 (HC-3). The effects of both compounds were determined in uiuo on rat brain acetylcholine (ACh), 'Y-choline (14C-Ch) incorporation into 14C-acetylcholine (14C-ACh) and on one way jump box avoidance and escape behavior in naive and trained rats. In addition, the in vitro effects of both drugs were determined on choline acetyltransferase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…These alterations are constistent with abnormalities in phospholipid membrane synthesis and integrity, but may also reflect impaired ChAT function. By contrast, other studies have found no changes or regional elevations in ChAT activity, indicating the potential for variability and/or artifacts with the use of postmortem brain tissues (eg, differences in tissue quality, postmortem interval, patient medication history, appropriate age-matched controls, and/ or small cohort sizes) (Domino et al, 1973;McGeer and McGeer, 1977). Limitations with these early pharmacological and postmortem studies further support the need to develop subtype-selective mAChR and nAChR ligands.…”
Section: Introductionmentioning
confidence: 70%
“…These alterations are constistent with abnormalities in phospholipid membrane synthesis and integrity, but may also reflect impaired ChAT function. By contrast, other studies have found no changes or regional elevations in ChAT activity, indicating the potential for variability and/or artifacts with the use of postmortem brain tissues (eg, differences in tissue quality, postmortem interval, patient medication history, appropriate age-matched controls, and/ or small cohort sizes) (Domino et al, 1973;McGeer and McGeer, 1977). Limitations with these early pharmacological and postmortem studies further support the need to develop subtype-selective mAChR and nAChR ligands.…”
Section: Introductionmentioning
confidence: 70%
“…We have used RC-3 and acetylseco HC-3 to inhibit the synthesis of ACh. Acetylseco RC-3 is used preferentially because of its dual mechanisms of action (inhibition of choline uptake and choline acetyltransferase), it provides less variability, and it is less toxic (42) .…”
Section: Pergamon Pressmentioning
confidence: 99%
“…Acetylcholinesterase has been tested in vitro as a predictor of the toxic potential of pesticides like organophosphate and carbamate compounds in white rats (El-Sebae et al, 1977;Chin et al, 1980) and goats (Guhathakurta and Bhattacharya, 1989). Besides pesticides, various psychotropic agents are known to influence the brain acetylcholineacetylcholinesterase concentration in rats (Naik and Sheth, 1970;Domino et al, 1973) and mice (Chabrier and Jacob, 1980). Some steroid contraceptives are found to decrease midbrain AChE activity (Bandyopadhyay and Ghosh, 1988).…”
Section: Introductionmentioning
confidence: 97%